MANAGEMENT OF EXTRACURRICULAR ACTIVITIES IN THE FORMATION OF STUDENT CHARACTER AT MUHAMMADIYAH 21 HIGH SCHOOL IN TEBING TINGGI - Elfin Nazri; Mardianto Mardianto; Neliwati Neliwati (Universitas Indraprasta PGRI, 2023)
The purpose of this research is to find out the management of extracurricular activities in the formation of students' character, namely extracurricular activities in character education which are very important to gain direct experience. Learners are actively involved and provide enough time outside of effective class hours so that value education is more accommodated through extracurricular activities. This research uses descriptive qualitative research using case study method. This research was conducted at SMA Muhammadiyah 21 Kota Tebing Tinggi with two sources of data, namely secondary and primary data with data collection techniques used interviews, observation, and documentation. Data were analyzed using data reduction techniques, data presentation and then data verification. To check the validity of the data, the techniques used are source triangulation, method triangulation, and theory triangulation. The results of this study reveal the findings: 1) extracurricular activity planning in the formation of student character, 2) implementation of extracurricular activities in the formation of student character, 3) assessment of extracurricular activities in the formation of student character. It was concluded that, in the process of planning extracurricular activities carried out according to what was targeted by the school. Extracurricular activities are carried out every Monday to Saturday outside of school hours and do not interfere with the ongoing teaching and learning process in the classroom so that students can follow their interests and talents. In extracurricular activities the implementation has been determined and regulated by the coach. Extracurricular activities for new methods or improving old methods, and also provide motivation in the form of criticism and suggestions that are conveyed by coaching to students.